Duane Michals - Couëlle, Jennifer (CV Photo)

(untitled) (Les Productions Ciel variable, 1998)
Summary We think of him when we think of photographic mise en scène - and of narrative sequences, and of the integration of handwriting into photographs. When Duane Michals made his first photographic fictions in the mid-sixties, the practice was not entirely without precedent. Hippolyte Bayard's Autopotrait en noyé dates back to 1840; then, there were the metaphor-ic experiments of futurist, surrealist, and Bauhaus photography, Moholy-Nagy's "productive creativity," and so on. True, but it was following Michals's first black-and-white still-lifes that the fabricated image began to be established as a trend. Traduction Käthe Roth